Evaluation of the nutritional impact and the organoleptic aceptance of enriched cookies with whey, soy and macadamia nuts in preschool children of commnity of Chiapas, Mexico - López-Villafuerte, Karla Berenice (Universidad Autónoma de Tamaulipas, 2013)
Whey contains 4.7 g of lactose (main component), followed by proteins with a high proportion of sulfur amino acids, which contribute to a high nutritional quality. The objective of this study was to assess the nutritional and sensory impact of enriched cookies with whey, soy, and macadamia nuts in preschool children from Chiapas, Mexico. Initially, we determined the nutritional status of children in a kindergarten from Tuxtla Gutiérrez, Chiapas. Later, the children who reported problems of undernutrition were fed for a period of three months with a cookie elaborated from whey, soy, and macadamia nuts. Four formulations were evaluated with sensorial acceptance of 95 % (P < 0.05), selecting the one with the greatest level of acceptance. At the middle and the end of the study, the nutritional status of the preschool children was evaluated. Proximal analysis determined the nutritional composition of the cookie, and the degree of acceptability by preference test with untrained judges. Fifty percent of total fed children showed improvement in their nutritional status (P < 0.05). Proximal analysis of the cookie showed a 75.56 % moisture, 0.27 % ash, 0.84 % fat, 12.95 % protein, 2.01 % fiber, and 8.37 % carbohydrates. The high degree of acceptability and the improvement in the nutritional status of the children fed revealed the viability of the cookie to be consumed by children suffering from malnutrition in underserved communities.